Cytokine dysregulation in children with severe neurological impairment correlates with significant clinical outcomes - Allen, John; Isaza-Correa, Johana; Kelly, Lynne; Melo, Ashanty; Power, Conor; Mahony, Aoife; McDonald, Denise; Molloy, Eleanor J. (Frontiers in Pediatrics, 2025)
BackgroundChildren with neurological disorders have altered inflammatory responses. We aimed to describe pro-inflammatory, anti-inflammatory and hypoxia-induced cytokines in serum, at baseline, and in response to stimulation of whole blood with lipopolysaccharide, in children with Severe Neurological Impairment (SNI) compared to controls.MethodsWhole blood samples from children with SNI and healthy controls were incubated in the presence or absence of lipopolysaccharide (LPS). Serum was isolated and 12 cytokines were analysed by ELISA. Select clinical data was collected from healthcare records and correlated with cytokine results.ResultsTwenty-nine children with SNI (n = 14) and age-matched controls (n = 15) were recruited. Cytokine responses to lipopolysaccharide were similar between the groups for Interferon (INF)-γ, Interleukin(IL)-18, Tumour Necrosis Factor(TNF)-β, IL-10, IL-1ra, IL-1β, IL-8, TNF-α and Vascular Endothelial Growth Factor (VEGF). Granulocyte Monocyte Colony Stimulating Factor (GM-CSF) increased in response to LPS in the control group (p = 0.04) but not in those with SNI (p = 0.07). The SNI cohort had a significantly greater increase in EPO in response to LPS than controls (p = 0.006). IL-6 in the SNI cohort was relatively hyporesponsive to LPS (p = 0.01). Correlations were found in LPS responses as follows: number of antiseizure medications and IL-1ra (p = 0.01) and TNF-α (p = 0.04); number of infections within the last year and IL-18 (p = 0.02); requirement for enteral feeding and IL-10 (p = 0.03) and EPO (p = 0.001); use of prophylactic antibiotics and IL-10 (p = 0.001); requirement for respiratory support and VEGF (p = 0.007).ConclusionChildren with SNI have persistent altered inflammatory responses. These alterations may contribute to tertiary neurological injury and impaired ability to respond to infection and may provide a target for immunomodulation.